(untitled) (Czech Journal of International Relations, 2003)
In this study, I treat globalization as one of the sources of the ongoing debate on the future of the European Union (EU). The existing analyses usually regard EU’s Eastern enlargement and the so-called democratic deficit of the EU decision-making as the two most important sources of this debate. However, the content of the documents and speeches that constitute the future of Europe debate reveals that EU political elite does also perceive globalization as an important incentive to define the finality of the European integration process and to reform EU institutions. My aim in this study is to provide a theoretically based explanation of why the debate is taking place, but I seek to provide only a limited explanation as I only deal with one of the sources of the debate: globalization. In the theoretical part, I discuss a constructivist approach to the relationship between globalization and European integration developed by Ben Rosamond, which I use as the theoretical framework of my analysis. This approach claims that globalization works as an important factor of the social construction of Europe and its external context. In this way, globalization leads to the emergence of a particular collective identity among EU political elite and reinforces the regional level as a valid space for policy-making. On the basis of this claim, I hypothesize that one of the sources of the ongoing effort to define the finality of European integration is a particular identity of EU political elite coming into existence in connection with globalization. In the empirical part, I test the hypothesis by making a discourse analysis based on the main documents of the European Commission and European Council and the speeches of the top British, French, and German state representatives on the future of the EU. The analysis confirms the hypothesis since it demonstrates that globalization is, indeed, interpreted by EU political elite as the process that takes place outside of Europe, defines Europe, and requires further deepening of European integration. Another finding of this study is, however, that it is relevant not only to test whether globalization leads to the emergence of a particular European identity, but also to examine what the content of that identity is. In his study, Rosamond describes that identity as the identity of Europe as a valid economic space. Nevertheless, the analysis of the globalization discourse within the future of Europe debate shows that there is yet another European identity based on globalization: the identity of Europe as a global actor. This case study focused on the future of Europe debate and it suggests, therefore, that not only does globalization enable the construction of Europe as a space for policy-making at the regional level, but it also leads to the construction of Europe as an actor at the global level of policy-making.